Zimbabwe’s Infrastructure : A Continental Perspective - Pushak, Nataliya; Briceno-Garmendia, Cecilia M. (2012)
Despite general economic decline and power-supply deficiencies, infrastructure made a modest net contribution of just less than half a percentage point to Zimbabwe's improved per capita growth performance in recent years. Raising the country's infrastructure endowment to that of the region's middle-income countries could boost annual growth by about 2.4 percentage points. Zimbabwe made significant progress in infrastructure in its early period as an independent state, building a national electricity network with regional interconnections, an extensive and internationally connected road network, and a water and sewer system. But the country has been unable to maintain its existing infrastructure since it became immersed in economic and political turmoil in the late 1990s. Zimbabwe now faces a number of important infrastructure challenges, the most pressing of which lie in the power and water sectors, where deteriorating conditions pose risks to the economy and public health. Zimbabwe currently spends about $0.8 billion per year on infrastructure, though $0.7 billion of this is lost to inefficiencies of various kinds. Even if these inefficiencies were fully captured, Zimbabwe would still face an infrastructure funding gap of $0.6 billion per year. That staggering figure can be reduced, however, to $0.4 billion if the country adopts a more modest spending scenario, or even to $0.1 billion under a minimalist, maintenance-only scenario. To close the gap, Zimbabwe needs to raise additional public, private-sector, and international funding, which, when coupled with the prospect of economic rebound and prudent policies, would allow the country to regain its historic infrastructure advantages.